Living a student-faculty partnership - Poon, Amy Fong-Yuk; O’Flynn-Magee, Kathy; Rodney, Patricia; Radu, Raluca; Turner, Hannah; Burnay, Marta; Griffin, Alanna; Dooner, Caryn; Esson, Lynne; Ong, Su Han; Proznick, Kate; Maitland, Skye; et al. (International Journal for Students as Partners, 2022)
Student and faculty collaborations are gaining recognition in higher education as an approach to optimise learning and the relationships embedded within education. However, existing hierarchies and power structures in academia often limit the nature of student-faculty partnerships. The student and faculty authors of this paper have an ongoing partnership within a project to address bullying in nursing education. The CRAB project (Cognitive Rehearsal to Address Bullying), is an initiative that is not only relevant for, and partnered with, students, but also initiated by them. The authors of this paper were interested in understanding what determined the success of the partnership. As a group, we reflect on the processes of collaboration, from creating innovative educational resources to co-authoring scholarly publications. Using verbatim quotes from the authors, we also explore the nature of the partnership along with the benefits and challenges from both student and faculty authors’ perspectives.